Evolution and Specificity of the Economic Institutions of Khanty-Mansi Autonomous Okrug - Yugra - Islamutdinov, Vadim Faruarovich (Economy of Regions, 2016)
The paper is dedicated to the study of the evolution of economic institutions in the resource-producing region, to the investigation of their specificity and institutional traps. As the initial data, the legal framework, the experience of the functioning of economic institutions and statistical data were used. The subject matter of the research is the influence of regional specificity on the evolution of economic institutions. The research topic is the analysis of the evolution, specificity and institutional traps of the economic institutions of the resource-producing region on the example of Khanty-Mansi Autonomous Okrug - Yugra. The purpose of the research is to identify the relationship between the regional specificity and the direction of the evolution of economic institutions. The hypothesis of the study is that the regional specificity has an impact on the evolution of economic institutions and contributes to the formation of institutional traps. The framework methodology of the work is a comparative institutional analysis. As a result, the stages of the evolution of economic institutions are determined, their regional specificity and institutional traps are revealed. The scientific input is in the revealing of the specificity of institutional traps at the regional level as well as the influence of specificity on the evolution of economic institutions. The author came to the conclusion that the specificity of the region’s economy affects the specificity of institutions as well as the formation of institutional traps. At the same time, some traps have a system-wide character and do not depend on the specificity of the region; this applies to the basic economic institutions. The most strongly the regional specificity is appeared in the evolution of the economic institutions for development, whose institutional traps are in many respects predetermined by the regional specificity. The results can be applied by the public administration at the regional level for the development and introduction of amendments to the legislation and further research. There is still the question of what comes first-the regional economic institutions or the economic development of the region, that is necessary to study both the co-evolution regional institutions and regional economics. Also, more research is needed to assess the impact of institutions on the level of transaction costs of economic entities.